Information architecture for IS function : a case study - Carriço, Nelson (2014)
Today’s complex, unstable and competitive society raises several difficulties to organisations. In this context, Information and Communications Technologies (ICT) and information itself have become resources of vital importance. The pressing need for Information Systems (IS) to meet several business requirements, in addition to the complexity involved in technology and business management, turns the IS Function one of the main areas of influence for success of modern organisations. Through its capacity of representing activities, management objects and corresponding relations, the Information Architecture of the Information Systems Function (IAISF), a technique derived from the well-known Information Architecture but exclusively focused on the Information Systems Function (ISF), allows not only the conceptualization and understanding of the ISF itself, but also of its interactions with other areas within organizations. This paper presents the main results of a case study related to the application of the IAISF technique in a computer service centre of a University.